HUBUNGAN KONSUMSI TABLET BESI (FE) DAN PENGETAHUAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS ALALAK TENGAH KOTA BANJARMASIN - Norfai Norfai (An-Nadaa: Jurnal Kesehatan Masyarakat (e-Journal), 2017)
Anemia is a condition in which the hemoglobin level in the blood is reduced or lower than normal which is less than 11.0 g / dl. Cases of iron deficiency anemia in pregnant women in Banjarmasin Middle Alalak Public Health Service occur an increasing which in 2012 amounted to 15.7%, in 2013 at a rate of 21.1%, while in 2014 amounted to 22.2%. This study aims to identify and explain the relationship of iron (Fe) tablet consumption and knowledge with the incidence of anemia in pregnant women in Banjarmasin Middle Alalak Public Health Service work area in 2015. This research is an analytic survey with cross sectional approach. The sample is at a rate of 120 respondents who visit and check up at a health facility of Middle Alalak Public Health Service work area. Data were collected through interviews using a questionnaire, data collected were analyzed using univariate and bivariate statistical chi square test using a computer program with a value of significance (a) 0.05. The study states that about 1 in 4 respondents did not have anemia during pregnancy. Variables that statistically has a significant relationship between maternal anemia (p-value ≤ 0.05) is the iron tablets Consumption and knowledge.